OLED material and application thereof

By using N-substituted triphenylene OLED materials as the main material for the light-emitting layer and combining them with carbazole derivatives as donors, the problem of poor stability caused by high triplet energy levels in blue OLED devices was solved, and a high-efficiency and long-lifetime blue light-emitting device was realized.

CN120865159APending Publication Date: 2025-10-31PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510802544.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In existing OLED devices, the high triplet energy level of blue emitting materials leads to poor stability, making it difficult to simultaneously meet the requirements of high efficiency and long lifespan.

Method used

Using N-substituted triphenylene OLED materials as the host material for the emitting layer, and combining carbazole and its derivatives as donors, efficient confinement of triplet excitons is achieved by optimizing the LUMO electron cloud distribution and triplet energy levels, thereby improving molecular stability.

Benefits of technology

It improves the efficiency and lifespan of blue light-emitting devices, enhances the electron transport capability of molecules, and ensures the high thermal stability of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120865159A_ABST
    Figure CN120865159A_ABST
Patent Text Reader

Abstract

The invention relates to an OLED material and application thereof. The OLED material provided by the invention adopts N-substituted triphenylene as an electron acceptor and carbazole and a derivative thereof as electron donors, is a main body material of long-life triplet excitons, can limit high-energy excitons, and has sub-second triplet lifetime. When the material is used as a luminescent layer main body material of a luminescent device, relatively high device efficiency can be obtained, and the service life is relatively long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromechanical light-emitting devices (OLEDs), specifically an OLED material and its applications. More particularly, it relates to a long-lifetime triplet-state host material capable of recycling the triplet state of blue emitting materials and its application in the fabrication of blue emitting devices. Background Technology

[0002] Organic light-emitting diodes (OLEDs), as a mature new display technology, have achieved large-scale commercialization and have become the mainstream technology for small and medium-sized displays. In OLED devices, electrons and holes are injected through electrodes and recombine in organic molecules to form excitons, which then emit light through radiation. According to the Pauli exclusion principle and the rules of spin statistics, during electrical driving, carrier recombination in the emitting layer produces singlet and triplet excitons in a 1:3 ratio. Therefore, fully utilizing the singlet and triplet excitons is essential for obtaining high-efficiency light-emitting devices. Currently, the main approaches are: 1) fluorescent materials that improve luminous efficiency by converting the non-directly luminescent triplet state into a luminescent singlet state through triplet-triplet recombination (TTA); 2) phosphorescent materials that utilize heavy atoms to induce triplet luminescence; and 3) TADF materials, which use molecular design to control the separation of HOMO and LUMO energy levels, thereby achieving effective inversion from triplet to singlet states. These materials can fully utilize all excited states, thus significantly improving OLED efficiency. However, the luminous efficiency and long-term stability of OLED devices still face bottlenecks that are difficult to achieve simultaneously. In particular, in blue OLEDs with high exciton energy, the low lifespan of high-efficiency devices due to the poor stability of traditional materials has been limiting the further development of OLED technology.

[0003] Currently, blue light-emitting devices generally use phosphors (TTA) as the emitting guest, which have low triplet exciton levels. However, if TADF, multiple resonance narrow-band blue fluorescent materials, or blue phosphorescent materials are used, they all possess higher triplet energy levels (E). T However, high E T Materials with these properties typically exhibit poor stability because their E... T These molecules approach the bond dissociation energy (BDE) of the molecule, making them unstable in the excited state and leading to poor device lifetime. Therefore, the most anticipated breakthrough and challenge currently lies in how to solve the problem of high Edegradation. T The dilemma of reconciling with molecular stability. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide an OLED material and its applications. The OLED material provided by this invention is a host material for long-lifetime triplet excitons, capable of confining high-energy excitons and possessing a sub-second triplet lifetime. Using this material as the host material for the emitting layer of a light-emitting device can achieve high device efficiency and a long lifetime.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] An OLED material, characterized in that the structure of the OLED material is as shown in the following formulas:

[0007]

[0008] In the above formulas, D is the electron donor and A is the electron acceptor.

[0009] Based on the above scheme, the electron donor includes the following groups:

[0010]

[0011] The electron acceptor is an N-substituted triphenylene, the structure of which is shown in the following formula:

[0012]

[0013] In the above triphenylene structure, any C atom numbered 1'-6' is connected to formula (I) or formula (II);

[0014] The N substitution refers to the fact that at least one C atom in the C atoms numbered 1-6 is replaced by N.

[0015] Based on the above scheme, the structure of the N-substituted triphenylene comprises:

[0016]

[0017] This invention utilizes N-substituted triphenylene as the acceptor (A), resulting in the LUMO electron cloud of the molecule being distributed within the triphenylene. Triphenylene possesses a high triplet energy level and sub-second triplet lifetime, thus effectively confining the excitons of narrow-band compounds such as BN in TADF blue luminescent materials or blue phosphorescent materials. Using carbazole and its derivatives as donors (D) endows the molecule with good charge transport capabilities.

[0018] A light-emitting device, using the above-mentioned OLED material, characterized in that the structure of the light-emitting device is as follows:

[0019] The material consists of an ITO conductive glass substrate, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole / exciton blocking and electron transport layer, an electron injection layer, and a cathode layer, stacked sequentially; wherein the light-emitting layer material contains the aforementioned light-emitting material.

[0020] The OLED material and its application described in this invention have the following beneficial effects:

[0021] In OLED materials, the LUMO of the N-triphenylene structure is distributed within the triphenylene, which enhances the electron transport capability of the molecule. N substitution does not alter the high triplet energy level of triphenylene, effectively confining triplet excitons. The triphenylene structure itself possesses a long-lived triplet state property, effectively improving device performance and stability. The high thermal stability of triphenylene ensures the material exhibits ultra-high thermal stability. Blue light-emitting devices fabricated using this OLED material exhibit high efficiency and long lifetime. Attached Figure Description

[0022] The present invention includes the following figures:

[0023] Figure 1 This is the general structural formula for the OLED material described in this invention.

[0024] Figure 2 The specific structure of the OLED material described in this invention is (based on diphenylcyclohexane with A and D groups connected together, where the A group is a 2N-substituted triphenylene, compounds H1-H8).

[0025] Figure 3 The specific structure of the OLED material described in this invention is (based on fluorene with A and D groups connected together, where the A group is a 2N-substituted triphenylene, compound H9-H16).

[0026] Figure 4 The specific structure of the OLED material described in this invention (based on diphenylcyclohexane with A and D groups connected, where the A group is a 4N-substituted triphenylene, compound H17-H24)

[0027] Figure 5 The specific structure of the OLED material described in this invention is based on diphenylcyclohexane with A and D groups connected together, where the A group is a 6N-substituted triphenylene, compound H25-H32.

[0028] Figure 6 The specific structure of the OLED material described in this invention is (based on fluorene with A and D groups connected together, where the A group is a 4N-substituted triphenylene, compound H33-H40).

[0029] Figure 7 The specific structure of the OLED material described in this invention is (based on fluorene with A and D groups connected together, where the A group is a 6N-substituted triphenylene, compounds H41-H48).

[0030] Figure 8 This is the LUMO electron cloud distribution diagram of compound H12 described in this invention. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the accompanying drawings. The various embodiments are used to further illustrate the content of the present invention, but should not be construed as limiting the present invention. Unless otherwise specified, the raw materials used are all purchased.

[0032] Example 1: Preparation of compound H1

[0033]

[0034] In a 250 mL three-necked round-bottom flask, PO (5.77 g, 27.7 mmol) was dissolved in 80 mL of methanesulfonic acid. N-bromosuccinimide (NBS) (4.93 g, 27.7 mmol) was slowly added in small increments over 30 min. The solution was stirred overnight at room temperature. The reaction was then terminated by pouring the solution into a mixture of ice and water, resulting in an orange precipitate. The precipitate was dissolved in dichloromethane and subsequently washed with saturated sodium bicarbonate solution. The solvent was removed under reduced pressure, and the product was purified by column chromatography (dichloromethane:petroleum ether = 2:1) to give the compound PO-Br.

[0035] In a 250 mL three-necked round-bottom flask, PO-Br (1.56 g, 5.46 mmol) and ethylenediamine (328 mg, 5.46 mmol) were added to 100 mL of acetic acid (AcOH). The reaction mixture was heated to 125 °C and stirred for 24 hours under nitrogen protection. After cooling to room temperature, the mixture was diluted with 100 mL of deionized water, and the crude product was obtained by suction filtration. The crude product was then recrystallized from hot ethanol. Finally, 1.57 g (4.05 mmol) of QP-Br product was obtained, with a yield of 74%.

[0036] In a 250 mL single-necked flask, 4 g of QP-Br (12.89 mmol, 1 eq), 3.93 g of diboronyl dihydrochloride (15.47 mmol, 1.2 eq), and 7.59 g of potassium acetate (77.31 mmol, 6 eq) were added sequentially, followed by 80 mL of 1,4-dioxane. The mixture was frozen in liquid nitrogen and evacuated for 5 min. Then, 1.05 mg (7.59 mmol, 0.1 eq) of [1,1'-bis(diphenylphosphine)ferrocene]palladium(II) dichloromethane was added to combine with Pd(dppf)2Cl2. The mixture was subjected to a freeze-thaw cycle twice under vacuum and reacted at 85 °C for 48 h. After the reaction was complete, water was added, and the mixture was extracted with dichloromethane. The organic phase was evaporated to dryness, and the mixture was stirred with silica gel. Petroleum ether:dichloromethane = 3:1 was used as the eluent to give compound QP-PZ in 61% yield.

[0037] 1,1-Bis(4-aminophenyl)cyclohexane (HN) (5.33 g, 20 mmol) was dissolved in H₂SO₄ (25%, 47 g), and then an aqueous solution of NaNO₂ (2.97 g, 43 mmol, 15 mL) was added dropwise to the mixture at 0 °C. The reaction mixture was stirred at this temperature for 2 hours, and then an aqueous solution of KI (8.63 g, 52 mmol, 100 mL) was slowly added dropwise at 50 °C. After stirring for 12 hours, the mixture was extracted three times with dichloromethane. The combined organic phases were washed with an aqueous solution of Na₂S₂O₃ and dried over anhydrous Na₂SO₄. After removing the solvent under vacuum, the mixture was purified by column chromatography on silica gel using petroleum as the eluent to give a white solid HPI (3.3 g, yield: 34%). 1 H NMR (500MHz, CDCl3, ppm): δ = 7.58 (d, J = 5Hz, 4H), 6.99 (d, J = 10Hz, 4H), 2.20–2.18 (m, 4H), 1.55–1.48 (m, 6H).

[0038] HPI (0.73 g, 1.5 mmol), 3,6-diphenyl-9H-carbazole (Cz) (0.41 g, 1.3 mmol), Pd2(dba)3 (80 mg, 0.09 mmol), (t-Bu)3PH-BF4 (100 mg, 0.36 mmol), and t-BuONa (0.58 g, 6 mmol) were added to ultra-dry toluene (30 mL), and the mixture was stirred under argon reflux for 24 h. After cooling to room temperature, the mixture was extracted three times with dichloromethane. The combined organic phases were washed with brine and dried over anhydrous Na2SO4. After removing the solvent under vacuum, the mixture was purified by column chromatography on silica gel using petroleum / dichloromethane = 1 (v / v) as the eluent to give a white solid HP-Cz (0.88 g, yield: 74%). 1 H NMR (500MHz, CDCl3) δ8.19 (s, 4H), 7.87 (s, 1H), 7.75 (s, 9H), 7.73–7.41 (m, 21H), 7.39 (d, J = 15.0Hz, 7H), 7.46–7. 11(m,13H),7.33(d,J=50.0Hz,10H),7.28(s,4H),7.01(s,4H),1.98(s,4H),1.59(d,J=9.7Hz,10H),1.12(s,6H).

[0039] In a 100 mL single-necked flask, 1.5 g of HP-Cz (2.21 mmol, 1 eq), 0.79 g of QP-PZ (2.21 mmol, 1 eq), 24 mL of toluene, 16 mL of 2 mol / L K₂CO₃ aqueous solution, and 8 mL of ethanol were added sequentially. After freezing, the mixture was evacuated for 5 min, and then 180 mg of tetra(triphenylphosphine)palladium (0.16 mmol, 0.05 eq) was added. The mixture was subjected to a freeze-thaw cycle twice, followed by evacuation at 90 °C for 16 h. After the reaction was complete, water was added and stirred for 5 min. The mixture was extracted with dichloromethane, evaporated to dryness, and then subjected to Al₂O₃ column chromatography with petroleum ether:dichloromethane = 1:1 as the eluent. The final product, H₁, was 1.26 g. 1 H NMR(500MHz, CDCl3)δ9.10(s,4H),8.97(t,J=2.4Hz,11H),8.76(s,4H),8.42(s,4H),8.10(s,4H),7.93(d,J=70.1Hz,12H),7.84–7.65(m,23 H),7.60(d,J=15.0Hz,7H),7.54–7.40(m,39H),7.40–7.27(m,17H),7.27–7.14(m,3H),2.03(s,7H),1.62(d,J=21.5Hz,20H),1.12(s,10H).

[0040] Example 2 Preparation of compound H9

[0041]

[0042] 9,9-bis(4-bromophenyl)-9H-fluorene (Wu) (0.71 g, 1.5 mmol), 9H-carbazole (Cz) (0.22 g, 1.3 mmol), Pd2(dba)3 (80 mg, 0.09 mmol), (t-Bu)3PH-BF4 (100 mg, 0.36 mmol), and t-BuONa (0.58 g, 6 mmol) were added to ultra-dry toluene (30 mL) and stirred under argon for 24 h under reflux. After cooling to room temperature, the mixture was extracted three times with dichloromethane. The combined organic phases were washed with brine and dried over anhydrous Na2SO4. After removing the solvent under vacuum, the mixture was purified by column chromatography on silica gel using petroleum / dichloromethane = 1 (v / v) as the eluent to give a white solid Wu-PZ (0.56 g, yield: 74%). 1H NMR (400MHz, CDCl3): δ (ppm): 8.122 (d, J = 7.6Hz, 2H), 7.821 (d, J = 7.6Hz, 2H), 7.471 (d,J=7.6Hz,2H),7.444-7.327(m,14H),7.286-7.246(m,2H),7.185-7.150(m,2H).

[0043] In a 100 mL single-necked flask, 1.28 g of Wu-Cz (2.21 mmol, 1 eq), 0.79 g of QP-PZ (2.21 mmol, 1 eq), 24 mL of toluene, 16 mL of 2 mol / L K₂CO₃ aqueous solution, and 8 mL of ethanol were added sequentially. After freezing, the mixture was evacuated for 5 min, and then 180 mg of tetra(triphenylphosphine)palladium (0.16 mmol, 0.05 eq) was added. The mixture was subjected to a freeze-thaw cycle twice, followed by evacuation at 90 °C for 16 h. After the reaction was complete, water was added and stirred for 5 min. The mixture was extracted with dichloromethane, evaporated to dryness, and then subjected to Al₂O₃ column chromatography with petroleum ether:dichloromethane = 1:1 as the eluent. 1.26 g of product H9 was finally obtained. 1 H NMR (500MHz, CDCl3) δ7.38 (d, J=8.1, 6.9, 1.5Hz), 7.43 (d, J=8.5, 6.2, 2.6H z),7.44(d,J=8.4,1.6,0.5Hz),7.47(d,J=8.2,6.2,1.5Hz),7.53(d,J=8.5 ,1.9,0.5Hz),7.62(d,J=8.5,1.8,0.5Hz),7.64(d,J=8.1,1.4,0.5Hz),7.7 4(d,J=8.2,2.6,0.5Hz),7.77(d,J=8.4,1.6,0.5Hz),7.77(d,J=8.5,1.5,0 .5Hz),7.85(d,J=8.5,1.5,0.5Hz),7.91(d,J=8.5,7.8,2.2Hz),8.02(d,J= 8.6,1.9Hz),8.06(d,J=8.6,7.8,2.2Hz)),8.38-8.58(2H,8.44(d,J=8.5,2 .2,0.5Hz),8.52(d,J=8.6,0.5Hz)),8.67(1H,d,J=8.6,2.2,0.5Hz),8.79( 1H, d, J = 1.9, 0.5 Hz), 9.19-9.34 (2H, 9.24 ( d, J = 7.0 Hz), 9.28 ( d, J = 7.0 Hz)).

[0044] Example 3 Preparation of compound H17

[0045] In a 100 mL single-necked flask, 1.5 g of HP-PCz (2.21 mmol, 1 eq), 0.80 g of 4QP-PZ (2.21 mmol, 1 eq), 24 mL of toluene, 16 mL of 2 mol / L K₂CO₃ aqueous solution, and 8 mL of ethanol were added sequentially. After freezing, the mixture was evacuated for 5 min, and then 180 mg of tetra(triphenylphosphine)palladium (0.16 mmol, 0.05 eq) was added. The mixture was subjected to a freeze-thaw cycle twice, followed by evacuation at 90 °C for 16 h. After the reaction was complete, water was added and stirred for 5 min. The mixture was extracted with dichloromethane, evaporated to dryness, and then subjected to silica gel column chromatography with petroleum ether:dichloromethane = 1:1 as the eluent. 1.15 g of product H17 was finally obtained. 1 H NMR(500MHz,DMSO)δ9.98(s,22H),9.04–9.00(m,44H),8.51(s,39H),8.30(s,22H),8.19(s,44H),8.15–7.79(m,94H),7.96–7.79(m,3H) ,7.79–7.70(m,155H),7.49(s,87H),7.41(s,64H),7.32(s,41H),7.28(s,41H),2.01(s,33H),1.69(s,57H),1.61(s,52H),1.18(s,59H).

[0046] Example 4 Preparation of compound H33

[0047]

[0048] In a 100 mL single-necked flask, 1.28 g of Wu-PCz (2.21 mmol, 1 eq), 0.79 g of 4QP-PZ (2.21 mmol, 1 eq), 24 mL of toluene, 16 mL of 2 mol / L K₂CO₃ aqueous solution, and 8 mL of ethanol were added sequentially. After freezing, the mixture was evacuated for 5 min, and then 180 mg of tetra(triphenylphosphine)palladium (0.16 mmol, 0.05 eq) was added. The mixture was subjected to a freeze-thaw cycle twice, followed by evacuation at 90 °C for 16 h. After the reaction was complete, water was added and stirred for 5 min. The mixture was extracted with dichloromethane, evaporated to dryness, and then subjected to silica gel column chromatography with petroleum ether:dichloromethane = 1:1 as the eluent. The final product, H₃₃, was 1.31 g. 1H NMR (500MHz, DMSO) δ9.01–8.97(m,3H),8.50(d,J=19.9Hz,6H),8.16(s,3H),8.09(s,2H),7.91(s,3H),7.69(s,3H),7.57(d,J=19.9H z,4H),7.47(s,3H),7.38(s,3H),7.36–7.23(m,9H),7.14(d,J=10.0Hz,5H),2.30(s,2H),2.11(s,1H),1.46(dd,J=29.9,19.9Hz,9H).

[0049] Compounds H1-H48, other than those listed in the above examples, can be prepared using similar methods. These compounds (structures as shown in the examples) Figures 2 to 7 The structures shown are representative of the spirit and principles of this invention. It should be understood that listing these compound structures is only for better explanation of this invention and is not intended to limit the invention.

[0050] The HOMO and LUMO energy levels and triplet T1 energy level performance of the above compounds are summarized in Table 1 below:

[0051] Table 1. Summary of HOMO and LUMO energy levels and triplet T1 energy level performance for each compound.

[0052]

[0053] In this invention, compounds H1, H3, H6, H8, H9, H11, H14, and H16 from Table 1 are selected as the main materials for the light-emitting layer of the blue organic electroluminescent device.

[0054] The long-lifetime triplet exciton material provided by this invention can be used as the main material for fabricating blue light-emitting devices, applied to the light-emitting layer of the device. The fabricated blue light-emitting device generally comprises, in sequence, an ITO conductive glass substrate (anode), a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole / exciton blocking and electron transport layer, an electron injection layer, and a cathode layer. The molecular structural formulas of some organic compounds used in this device are shown below:

[0055]

[0056] Example 5: Fabrication of a Blue Light-Emitting Reference Device

[0057] a) Cleaning ITO (Indium Tin Oxide) Glass: Ultrasonically clean the ITO glass for 20 minutes each with deionized water, acetone and ethanol, and then treat it in an oxygen plasma cleaner for 2 minutes.

[0058] b) A hole injection layer, such as HATCN, with a thickness of 5 nm, is deposited on the anode ITO glass; a hole transport layer, such as TAPC, with a thickness of 40 nm; an electron blocking layer, such as TCTA, with a thickness of 5 nm; a light-emitting layer, such as mCBP (reference device 1), mSiTRz (reference device 2), and 26DCzPPy (reference device 3), is doped with guest BD-02 at a ratio of 11 wt%, with a thickness of 20 nm; an exciton blocking and electron transport layer, such as TmPyPB, with a thickness of 30 nm; an electron injection layer, such as LiF, with a thickness of 1 nm; and a cathode, such as Al, with a thickness of 150 nm. The photoelectric data, such as the turn-on voltage, maximum current efficiency, maximum brightness, and CIE color purity of the fabricated blue light reference devices 1 to 3, are listed in the table below.

[0059] Example 6: Blue light-emitting device using compound Hn as the main material of the light-emitting layer

[0060] Blue light-emitting devices four to eleven were prepared by replacing the exciton blocking and electron transport layers in the reference device of Example 3 with compounds H1, H3, H6, H8, H9, H11, H14, and H16, respectively, according to the method described in Example 3.

[0061] The photoelectric data, such as the turn-on voltage, maximum current efficiency, maximum brightness, and CIE color purity, of the blue light-emitting reference devices one to three prepared in Example 3, and the blue light-emitting devices four to eleven prepared in Example 4 are listed in Table 2.

[0062] Table 2 Optical performance of blue light-emitting devices

[0063]

[0064] Of course, the functional layers of the device of the present invention are not limited to the above-mentioned materials. These materials can be replaced by other materials. For example, the electron transport layer can be TPBi, DPPS, etc., the hole transport layer can be TPD, BPBPA, DTASi, etc., and the blue light guest can also be phosphorescent materials such as Fir6, Firtaz, FirN4, Firpic, Ir(dpt)3, etc., or deep blue light resonant TADF guest ν-DABNA, t-DABNA, etc. The molecular structural formulas of these materials are shown below:

[0065]

[0066] The contents not described in detail in this specification are existing technologies known to those skilled in the art.

Claims

1. An OLED material, characterized in that, The structure of the OLED material is shown in the following formulas: In the above formulas, D is the electron donor and A is the electron acceptor.

2. The OLED material as described in claim 1, characterized in that: The electron donor D includes the following groups: The electron acceptor A is an N-substituted triphenylene, the structure of which is shown in the following formula: In the above triphenylene structure, any C atom numbered 1'-6' is connected to formula (I) or formula (II); The N substitution refers to the fact that at least one C atom in the C atoms numbered 1-6 is replaced by N.

3. The OLED material as described in claim 2, characterized in that: The structure of the N-substituted triphenylene comprises:

4. A light-emitting device, using the OLED material according to any one of claims 1-3, characterized in that, The structure of the light-emitting device is as follows: The material comprises, in sequence, an ITO conductive glass substrate, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole / exciton blocking and electron transport layer, an electron injection layer, and a cathode layer; wherein the light-emitting layer material contains the light-emitting material described in any one of claims 1-3.